Capital Inflows, Equity Issuance Activity, and Corporate Investment - Calomiris, Charles W. (World Bank, Washington, DC, 2018)
This paper uses issuance-level data to study how equity capital inflows that enter emerging market economies affect equity issuance and corporate investment. It shows that foreign inflows are strongly correlated with country-level issuance. The relation reflects the behavior of large issuers issuing in domestic equity markets and that of firms issuing in international markets. Those larger, more liquid, and highly valued firms are the ones more likely to raise equity when their country receives capital inflows. To identify supply-side shocks, capital inflows into each country are instrumented with exogenous changes in other countries' attractiveness to foreign investors. Shifts in the supply of foreign capital are important drivers of increased equity inflows. Instrumented inflows lead a subset of firms (large domestic issuers and foreign issuers) to raise new equity, which they use to fund investment. Corporate investment increases between one-tenth and four-tenths the amount of foreign equity capital entering the country.